2016
DOI: 10.1371/journal.ppat.1005564
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus gH/gL Forms a Stable Complex with the Fusion Protein gB in Virions

Abstract: Human cytomegalovirus (HCMV) is a ubiquitous virus that is a major pathogen in newborns and immunocompromised or immunosuppressed patients. HCMV infects a wide variety of cell types using distinct entry pathways that involve different forms of the gH/gL glycoprotein: gH/gL/gO and gH/gL/UL128-131 as well as the viral fusion glycoprotein, gB. However, the minimal or core fusion machinery (sufficient for cell-cell fusion) is just gH/gL and gB. Here, we demonstrate that HCMV gB and gH/gL form a stable complex earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 46 publications
2
81
0
Order By: Relevance
“…Previous work has shown that HCMV gB and/or gH interacts with THY-1 (29) and integrins (30,104). In addition, a gH/gL/gB complex is present in HCMV particles (10). Therefore, THY-1 and integrins might cooperatively mediate HCMV internalization by bridging virus attachment with macropinocytosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work has shown that HCMV gB and/or gH interacts with THY-1 (29) and integrins (30,104). In addition, a gH/gL/gB complex is present in HCMV particles (10). Therefore, THY-1 and integrins might cooperatively mediate HCMV internalization by bridging virus attachment with macropinocytosis.…”
Section: Discussionmentioning
confidence: 98%
“…The pentamer and trimer glycoprotein complexes interact with specific cellular receptors in a cell typedependent manner (8), which has been postulated to lead to the recruitment of gB and to trigger membrane fusion (9). However, a recent study showed that HCMV gH/gL and gB form stable gBgH/gL complexes that are incorporated into virions prior to receptor binding or membrane fusion and that only small amounts of gH/gL/gO and gH/gL/UL128-131A complexes are associated with gB (10).…”
mentioning
confidence: 99%
“…Recently, the HCMV gH/gL complex has been shown to form a stable complex with the fusion protein gB in virions including up to 50 % of total gH/gL, suggesting that gH/gL interacts with gB to mediate membrane fusion [65].…”
Section: Genetic Determinants Of Endothelial Cells and Leukocyte Tropismmentioning
confidence: 99%
“…Three of the viral glycoproteins are essential for fusion of herpesvirus envelopes with host cell membranes: the fusion protein gB and the glycoproteins gH and gL, presumably functioning as a trigger of gB fusion activity (7)(8)(9). In support of this model, Varnarsdall et al demonstrated recently that HCMV gH/gL and gB interact within the virus envelope (10). In contrast to gH/gL of herpes simplex virus (HSV) or Kaposi's sarcoma-associated herpesvirus (KSHV), HCMV gH/gL is stably bound to accessory proteins which are crucial for infection of different host cells.…”
mentioning
confidence: 94%